Identification of sodium channel toxins from marine cone snails of the subgenera Textilia and Afonsoconus - McMahon, Kirsten L.; O’Brien, Henrik; Schroeder, Christina I.; Deuis, Jennifer R.; Venkatachalam, Dhananjeyan; Huang, Di; Green, Brad R.; Bandyopadhyay, Pradip K.; Li, Qing; Yandell, Mark; Safavi-Hemami, Helena; Olivera, Baldomero M.; et al. (Cellular and molecular life sciences : CMLS, 2023)
Voltage-gated sodium (Na V ) channels are transmembrane proteins that play a critical role in electrical signaling in the nervous system and other excitable tissues. µ-Conotoxins are peptide toxins from the venoms of marine cone snails (genus Conus ) that block Na V channels with nanomolar potency. Most species of the subgenera Textilia and Afonsoconus are difficult to acquire; therefore, their venoms have yet to be comprehensively interrogated for µ-conotoxins. The goal of this study was to find new µ-conotoxins from species of the subgenera Textilia and Afonsoconus and investigate their selectivity at human Na V channels. Using RNA-seq of the venom gland of Conus ( Textilia ) bullatus, we identified 12 µ-conotoxin (or µ-conotoxin-like) sequences. Based on these sequences we designed primers which we used to identify additional µ-conotoxin sequences from DNA extracted from historical specimens of species from Textilia and Afonsoconus . We synthesized six of these µ-conotoxins and tested their activity on human Na V 1.1–Na V 1.8. Five of the six synthetic peptides were potent blockers of human Na V channels. Of these, two peptides (BuIIIB and BuIIIE) were potent blockers of hNa V 1.3. Three of the peptides (BuIIIB, BuIIIE and AdIIIA) had submicromolar activity at hNa V 1.7. This study serves as an example of the identification of new peptide toxins from historical DNA and provides new insights into structure–activity relationships of µ-conotoxins with activity at hNa V 1.3 and hNa V 1.7.